Induction of cell-mediated immunity during early stages of infection with intracellular protozoa - Gazzinelli,R.T. (1998)
Toxoplasma gondii and Trypanosoma cruzi are intracellular parasites which, as part of their life cycle, induce a potent cell-mediated immunity (CMI) maintained by Th1 lymphocytes and IFN-g. In both cases, induction of a strong CMI is thought to protect the host against rapid parasite multiplication and consequent pathology and lethality during the acute phase of infection. However, the parasitic infection is not eliminated by the immune system and the vertebrate host serves as a parasite reservoir. In contrast, Leishmania sp, which is a slow growing parasite, appears to evade induction of CMI during early stages of infection as a strategy for surviving in a hostile environment (i.e., inside the macrophages which are their obligatory niche in the vertebrate host). Recent reports show that the initiation of IL-12 synthesis by macrophages during these parasitic infections is a key event in regulating CMI and disease outcome. The studies reviewed here indicate that activation/inhibition of distinct signaling pathways and certain macrophage functions by intracellular protozoa are important events in inducing/modulating the immune response of their vertebrate hosts, allowing parasite and host survival and therefore maintaining parasite life cycles.